A cause for concern? Osteopoikilosis found incidentally in the emergency department: a case report. Issue 5 (23rd April 2007) - Bull, Matthew; Calderbank, Phil; Ramachandran, Navin
Abstract : Osteopoikilosis is a rare, inherited bone disorder, which is usually found incidentally on x ray. It may be mistaken for other, more serious disorders such as bony metastases, causing undue distress to the doctor and patient.